Sosialisasi Ekonomi Berkelanjutan Melalui Agribisnis Hidroponik - Mardhiah, Ainal; Wardani, Sari; Hasanah, Hasanah (Pencerah, 2025)
The sustainable economic socialization program through hydroponic agribusiness in Menasah Tutong Village aims to enhance the community's understanding and skills in implementing hydroponic farming systems as a modern agricultural solution. This initiative includes education, practical training, and ongoing mentoring for participants, particularly members of the PKK (Family Welfare Empowerment) group. The results indicate an increase in knowledge and skills in hydroponic cultivation, as well as business opportunities in the agricultural sector. Additionally, this program promotes food security and economic independence within the community. Although challenges such as limited resources and product marketing remain, this initiative has the potential to serve as a sustainable community empowerment model. In the future, long-term mentoring and collaboration with various stakeholders are essential to ensure the program's sustainability and its positive impact on the community.